Acceptability of asking patients about violence in accident and emergency. Issue 2 (1st March 2002) - Howe, A; Crilly, M; Fairhurst, R
Abstract : Objectives: To assess the acceptability to patients attending accident and emergency (A&E) of routine questioning about violence. Methods: A questionnaire survey (15 questions; 5 point Likert scale) was distributed to a representative sample of all adult patients attending a district general hospital A&E department, Lancashire, England over a seven day period. Results: 303 questionnaires were distributed and 281 returned questionnaires were available for analysis. Some 67% (95%CI 60% to 74%) of patients agreed that people attending A&E should routinely be asked about whether they have been assaulted. Altogether 89% (95%CI 85% to 93%) thought that health care staff should encourage victims of abuse or violence to inform the police, while 74% (95%CI 68% to 80%) thought that health care staff should routinely inform the police. While only 45% (95%CI 36% to 54%) of patients thought that people who had been assaulted would be likely to tell if asked, 81% (95%CI 76% to 86%) thought that if they themselves were victims they would tell if asked directly. Conclusions: Patients attending A&E departments support routine questioning by doctors and nurses about violence. They also support health professionals routinely informing the police in cases of violence. Further research is required into the outcomes of routine and direct questioning in A&E of patients about their exposure to violence.